FAKTOR-FAKTOR DETERMINAN STATUS GIZI IBU HAMIL - DIAN HANDAYANI (LPPM IAIN Parepare, 2014)
This paper discusses determinant factors of nutrition of pregnant women. Nutrition problems is a complex issue that is influenced by various factors, but from some intensive programs implemented, it have shown quite encouraging results such as reducing infant and under-five mortality, maternal mortality, and increasing life expectancy. The issue of maternal nutrition has broad implications, both for the mother and fetus. Some research shows a strong correlation between anemia during pregnancy and fetal death, abortion, birth defects, low birth weight, decreased iron stores in children or children born in nutritional anemia. This condition causes the rate of prenatal mortality is still high, including mother’s mortality and morbidity. In addition, the impact may cause bleeding during giving a birth. Bleeding at childbirth is the leading cause (28%) of maternal deaths in Indonesia. Whereby, Indonesian government committed to combat maternal anemia by doing “public nutrition improvement” program with a target prevalence of anemia in the year 2009 by 30%.